2020
DOI: 10.1212/nxi.0000000000000705
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of mycophenolate mofetil in myelin oligodendrocyte glycoprotein antibody-associated disorders

Abstract: ObjectiveTo investigate whether the use of mycophenolate mofetil (MMF) could reduce the relapse risk in patients with myelin oligodendrocyte glycoprotein (MOG)-immunoglobulin G (IgG)-associated disorders (MOGADs).MethodsThis prospective observational cohort study included patients with MOGAD at Peking Union Medical College Hospital between January 1, 2017, and April 30, 2019. The patients were divided into 2 groups: those with (MMF+) or without (MMF−) MMF therapy. The primary outcome was relapse at follow-up. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 33 publications
4
38
1
Order By: Relevance
“…However, due to the possible devastating side effects of long-term steroid administration, a switch to a steroid-sparing medication might be considered. Patients treated with immunosuppressants such as AZT (adjunctively with oral steroids), MMF and MTX presented better outcome in terms of relapses and disability [ 52 , 72 , 73 , 74 , 75 ]. The efficacy of RTX is not constant.…”
Section: Mogad Treatmentmentioning
confidence: 99%
“…However, due to the possible devastating side effects of long-term steroid administration, a switch to a steroid-sparing medication might be considered. Patients treated with immunosuppressants such as AZT (adjunctively with oral steroids), MMF and MTX presented better outcome in terms of relapses and disability [ 52 , 72 , 73 , 74 , 75 ]. The efficacy of RTX is not constant.…”
Section: Mogad Treatmentmentioning
confidence: 99%
“…A recent prospective observational study showed an impressive risk reduction of relapse due to treatment with mycophenolate mofetil (MMF). 133 This study included 79 MOG-IgG positive patients presenting with ADEM, optic neuritis, transverse myelitis and/or brainstem syndrome compatible with deymelination who received either MMF or no immune treatment based on consensual decision with the treating physician and were followed for a median of 400 days; additional treatment for the acute phase with steroid tappering was allowed. Multivariate analyses adjusting for potential confounders such as age, sex, previous disease course and initial level of MOG-IgG titre revealed that MMF treatment resulted in a reduced risk of relapse by 86%.…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…Multivariate analyses adjusting for potential confounders such as age, sex, previous disease course and initial level of MOG-IgG titre revealed that MMF treatment resulted in a reduced risk of relapse by 86%. 133 …”
Section: Clinical Aspectsmentioning
confidence: 99%
“… 68 , 69 Against this background, a prospective observational cohort study from China, although not a randomized trial, provides valuable clinical evidence on the effect of MMF on relapse rates in MOGAD. 70 Seventy-nine patients with MOGAD (children and adults, 54 on MMF and 25 without MMF; both groups had an additional and comparable steroid taper) were followed over a median of 261 days (without MMF) and 472.5 days (with MMF). Relapse rates were 7.4% in the w/ MMF group and 44% in the w/o MMF group.…”
mentioning
confidence: 99%